Pengaruh Permainan Tradisional Dalam Meningkatkan Keterampilan Sosial Siswa SMP - Purwaka Hadi; Abdullah Sinring; Farida Aryani (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
This study aims to determine the description of traditional games as a medium of counseling in improving the social skills of students and know the influence of traditional games as a medium of counseling in improving students' social skills. The research used quasi experiment with Pretest-Posttest Control Group Design design research. The samples used purposive sampling with 12 experimental group and 12 control group. Instrument using social skill scale. The findings of this study reveal that 1) the level of social skills of students in SMP Negeri 18 Makassar before being treated in the form of traditional games are in the